The Influence of Digital Technology Towards Student Involvement in Secondary School Co-Curricular Activities - Sheila Michael; Abdul Said Ambotang (2020)
This article reviews the concept of digital technology influences towards student involvement in secondary school co-curricular activities. Digital technology in this study covers all types of electronic devices, gadgets and applications that use the information in digital form including laptops, smartphones, as well as other high-tech devices. Although digital technology has its own benefits, it is said to have an impact on student's lifestyle. Co-curricular activities are less concerned by ignoring the importance of students' self-determination and self-esteem, thus affecting their educational development. Therefore, digital technology is found to have influence on student involvement in secondary school co-curricular activities.